Beam hardening artifacts of liquid embolic agents: comparison between Squid and Onyx. (19th December 2018) - Pop, Raoul; Mertz, Luc; Ilyes, Annamaria; Mihoc, Dan; Richter, Johann Sebastian; Manisor, Monica; Kremer, Stéphane; Beaujeux, Rémy
Abstract : Background: Initial clinical experience with Squid shows subjectively reduced artifacts on post-embolization CT scans compared with Onyx. To further investigate these observations, we aimed to perform a comparison of artifacts between Squid and Onyx in a controlled in vitro model. Materials and methods: Onyx 18 and all four variants of Squid (Squid 18, Squid 18 low density (LD), Squid 12, Squid 12 LD) were each injected in dimethylsulfoxide (DMSO) compatible test tubes. The tubes containing precipitated embolic material were inserted in a CT phantom for conventional and flat panel CT acquisitions. Beam hardening artifacts were quantified using objective and subjective measurements. Results: Objective evaluation of artifacts within regions of interest (ROIs) placed around the embolic material on CT and flat panel CT images demonstrated significantly lower noise and Hounsfield unit (HU) range values for all four Squid products compared with Onyx 18. On both CT and flat panel CT, LD variants of Squid 18 and Squid 12 had significantly lower noise and HU range values than their normal density counterparts on longitudinal ROIs. When using subjective measures for diagnostic value within ROIs placed around the embolic material on both CT and flat panel CT images, the number of non-diagnostic ROIs was significantly higher for Onyx 18 than for all four Squid variants. Conclusion: All four variants of Squid induced fewer beam hardening artifacts than Onyx 18 on CT and flat panel CT acquisitions. LD variants of Squid induced fewer artifacts than their normal density counterparts.